FNEP: Finnish-Nepalese Project for improving the meteorological readiness in Nepal - Mäkelä, Antti; Ylikangas, Irma; Karki, Ramchandra; Budhathoki, Kamal Prakash; Perrels, Adriaan; Säntti, Kristiina; Partio, Mikko; Keränen, Matti (Journal of Hydrology and Meteorology, 2016)
The Finnish Nepalese Project (FNEP) is a project aimed for the development of infrastructure, education and preparedness to better respond to the increased risks related to the weather-related natural disasters by climate change in Nepal. The project duration was 2010-2012, and the partners were the Finnish Meteorological Institute and the Government of Nepal, Ministry of Environment and Science, Department of Hydrology and Meteorology. The project is financed by the Finnish Ministry of Foreign Affairs. This paper introduces the concept and main results of the project. Journal of Hydrology and Meteorology, Vol. 8(1) 2012, p.72-76